Self-tolerance - Waldmann, Herman (Henry Stewart Talks, 2020)
Introduction to self-tolerance, Molecular basis of tolerance, Central and peripheral tolerance, Autoimmune diseases, Co-stimulation and co-inhibition, Experimental tolerance induction